Special Focus Introduction: Conceptualizing an Engaged Pastoral in Contemporary French and Francophone Literature - Melinda A Cro; Rachel Paparone (Studies in 20th & 21st Century Literature, 2018)
This special focus section seeks to examine and problematize contemporary pastoral works from the perspective of engagement. Despite assertions that the pastoral tends towards reductionism, the mode actually serves as a productive space wherein to examine issues like global warming, resource exploitation, and pollution. Through a range of texts and artistic projects, the authors of this section explore the nexus of engagement in contemporary pastoral production particularly with regard to the relationship between the human and the non-human.
Keywords: pastoral literature; engaged literature; ecocriticism; Lawrence Buell; Terry Gifford; French and Francophone literature